A Younger Dryas re-advance of local glaciers in north Greenland. (1st September 2016) - Larsen, Nicolaj K.; Funder, Svend; Linge, Henriette; Möller, Per; Schomacker, Anders; Fabel, Derek; Xu, Sheng; Kjær, Kurt H.
Abstract: The Younger Dryas (YD) is a well-constrained cold event from 12, 900 to 11, 700 years ago but it remains unclear how the cooling and subsequent abrupt warming recorded in ice cores was translated into ice margin fluctuations in Greenland. Here we present 10 Be surface exposure ages from three moraines in front of local glaciers on a 50 km stretch along the north coast of Greenland, facing the Arctic Ocean. Ten ages range from 11.6 ± 0.5 to 27.2 ± 0.9 ka with a mean age of 12.5 ± 0.7 ka after exclusion of two outliers. We consider this to be a minimum age for the abandonment of the moraines. The ages of the moraines are furthermore constrained using Optically Stimulated Luminescence (OSL) dating of epishelf sediments, which were deposited prior to the ice advance that formed the moraines, yielding a maximum age of 12.4 ± 0.6 ka, and bracketing the formation and subsequent abandonment of the moraines to within the interval 11.8–13.0 ka ago. This is the first time a synchronous YD glacier advance and subsequent retreat has been recorded for several independent glaciers in Greenland. In most other areas, there is no evidence for re-advance and glaciers were retreating during YD. We explain the different behaviour of the glaciers in northernmost Greenland as a function of their remoteness from the Atlantic Meridional Overturning Circulation (AMOC), which in other areas has been held responsible for modifying the YD drop in temperatures. Highlights: We dated moraines from local ice caps in North Greenland using 10 Be surface exposure dating and OSL. Moraine formation and subsequent abandonment between 11.8 and 13.0 ka ago. Synchronous Younger Dryas glacier advance at several glaciers. Review of Younger Dryas ice margin fluctuations in Greenland. Strong influence of Atlantic Meridional Overturning Circulation on ice margin fluctuations.